Fire safe use of wood in buildings : global design guide - Buchanan, Andrew; Östman, Birgit (CRC Press : Taylor & Francis Group, 2022)
This book provides guidance on the design of timber buildings for firesafety, developed within the global network Fire Safe Use of Wood (FSUW)and with reference to Eurocode 5 and other international codes. It introduces the behaviour of fires in timber buildings and describes strategies forproviding safety if unwanted fires occur. It provides guidance on buildingdesign to prevent any fires from spreading while maintaining the load-bearing capacity of structural timber elements, connections and compartmentation. Also included is information on the reaction-to-fire of wood productsaccording to different classification systems, as well as active measures offire protection, and quality of workmanship and inspection as means offulfilling fire safety objectives.This book: Presents global guidance on fire safety in timber buildings Provides a wide perspective, covering the whole field of fire safetydesign Uses the latest scientific knowledge, based on recent analytical andexperimental research results Gives practical examples illustrating the importance of good detailing in building designFire Safe Use of Wood in Buildings is ideal for all involved in the fire safetyof buildings, including architects, engineers, firefighters, educators, regulatory authorities, insurance companies and professionals in the buildingindustry